2011
DOI: 10.1002/cbdv.201000301
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils from Wild Populations of Algerian Lavandula stoechas L.: Composition, Chemical Variability, and in vitro Biological Properties

Abstract: In an effort to develop local productions of aromatic and medicinal plants, a comprehensive assessment of the composition and biological activities of the essential oils (EOs) extracted from the aerial flowering parts of wild growing Lavandula stoechas L. collected from eleven different locations in northern Algeria was performed. The oils were characterized by GC-FID and GC/MS analyses, and 121 compounds were identified, accounting for 69.88-91.2% of the total oil compositions. The eleven oils greatly differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 35 publications
2
54
1
4
Order By: Relevance
“…Several publications on antifungal activity of the essential oils against Malassezia species were reported in the literature (4,13,14). Our results are consistent with those found by Naeini et al (15) (22). In this study, the mean inhibition zones were found to be 14.4 and 12.4 mm for ketoconazole and fluconazole, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Several publications on antifungal activity of the essential oils against Malassezia species were reported in the literature (4,13,14). Our results are consistent with those found by Naeini et al (15) (22). In this study, the mean inhibition zones were found to be 14.4 and 12.4 mm for ketoconazole and fluconazole, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Aromatic species show a high adaptive capacity to various environments, as in the arid and semi-arid areas of the Mediterranean region. The different climatic and soil characteristics of the Mediterranean region influence the chemical composition of the EOs and many authors have found different compositions of EOs for the same species (7,14,(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…stoechas from other areas of the Mediterranean [South Sardinia (7), North Algeria (21) and North-East Greece (22)]. We chose these studies for comparison because the authors used similar extraction techniques and plant parts (Table 5).…”
mentioning
confidence: 99%
“…viridis and L . pedunculata that accumulate one of the richest blends of volatile compounds of all Lavandula species with more than 100 identified substances (Benabdelkader et al ). They are known for the diversity of their chemotypes that sometimes grow sympatrically.…”
Section: Introductionmentioning
confidence: 99%